Antimicrobial activities of leptospermone isolated from Leptospermum scoparium seeds and structure–activity relationships of its derivatives against foodborne bacteria - Jeong, Eun-Yong; Lee, Myung-Ji; Lee, Hoi-Seon (Food science and biotechnology, 2018)
This study was carried out to determine the antimicrobial activities of leptospermone isolated from Leptospermum scoparium and its derivatives against six foodborne bacteria ( Listeria monocytogenes , Salmonella typhimurium , Shigella flexneri , Shigella sonnei , Staphylococcus intermedius and Staphylococcus aureus ), with a view to developing safer antimicrobial agents. The essential oil of L. scoparium seeds possessed potent antimicrobial activity against six bacterial strains. The antimicrobial compound of L. scoparium was isolated by chromatographic analyses and identified as leptospermone. To investigate the structure–activity relationships, the antimicrobial activities of leptospermone and its derivatives (2-acetyl-1,3-cyclohexanedione, 1,3-cyclohexanedione, 1,2,3-cyclohexanetrione-1,3-dioxime, 5,5-dimethyl-1,3-cyclohexanedione and 2,2,4,4,6,6-hexamethyl-1,3,5-cyclohexanetrione) were examined against six foodborne bacteria. Based on the MIC values, leptospermone (MIC 23.6–69.7 μg/mL), 1,2,3-cyclohexanetrione-1,3-dioxime (MIC 43.9–88.5 μg/mL) and 2,2,4,4,6,6-hexamethyl-1,3,5-cyclohexanetrione (MIC 43.9–88.5 μg/mL) exhibited antimicrobial activities against the six foodborne bacteria. These results indicated that leptospermone and its derivatives could potentially be developed as natural food preservatives, rather than using hazardous synthetic preservatives.